Age validation of age 0-3 wild cod Gadus morhua in the western Baltic Sea through mark-recapture and tetracycline marking of otoliths - Krumme, Uwe; Stötera, Sven; McQueen, Kate; Pahlke, Erhard (Marine Ecology Progress Series, 2020)
The contrasting zones within otoliths are commonly used to infer age of fish, assuming that 1 opaque zone and 1 translucent zone (TZ) form per year. However, the periodicity of zone formation is often un-validated and susceptible to interpretation errors and uncertainties, which propagate into age-structured calculations. The western Baltic cod Gadus morhua (WBC) stock is currently evaluated through an age-based assessment, using the typical, temperate area assumption that TZs form in autumn/winter. The periodicity of zone formation was evaluated through a mark−recapture experiment with juvenile and young adult WBC. During 2014−2017, 9111 wild cod were tagged externally (T-bar anchor tag) and internally (injection with tetracyclinehydrochloride induced a permanent fluorescent mark on their otoliths) and released. Timing of TZ formation was reconstructed through examination of otoliths from recaptured age 0−3 cod for which all required information and otoliths were available (n = 59, length range: 173−500 mm). Contrary to the assumption that TZs are formed during winter, recaptured cod consistently formed 1 TZ per year, between summer and autumn, in both juveniles (age 0−1) and young adults (age 2−3). A calendar year in the otolith is therefore composed of a TZ with opaque material on either side. Coincidence of TZ formation and recent evidence of shallow-water avoidance and reduced feeding and growth in WBC during peak summer suggests that TZs are formed when metabolic demands cannot be met. The results improve accuracy of WBC age estimates and highlight the feasibility and importance of conducting age validation experiments.